2023
DOI: 10.3390/cells12111466
|View full text |Cite
|
Sign up to set email alerts
|

Response of Prolyl 4 Hydroxylases, Arabinogalactan Proteins and Homogalacturonans in Four Olive Cultivars under Long-Term Salinity Stress in Relation to Physiological and Morphological Changes

Aristotelis Azariadis,
Filippos Vouligeas,
Elige Salame
et al.

Abstract: Olive (Olea europeae L.) salinity stress induces responses at morphological, physiological and molecular levels, affecting plant productivity. Four olive cultivars with differential tolerance to salt were grown under saline conditions in long barrels for regular root growth to mimic field conditions. Arvanitolia and Lefkolia were previously reported as tolerant to salinity, and Koroneiki and Gaidourelia were characterized as sensitive, exhibiting a decrease in leaf length and leaf area index after 90 days of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 98 publications
0
3
0
Order By: Relevance
“…The same authors noted that transcriptional analyses have indicated a repression of cell wall-related gene expression including AGPs and xyloglucan, as a result of salt stress. Similarly, Azariadis et al [224] reported that immunodetection revealed a weak AGP signal in the 'Koroneiki' cultivar, which was associated with irregular cells and intercellular spaces, resulting in the formation of aerenchyma after 45 days of salt treatment. Hydroxyproline-rich cell wall glycoproteins (HRGP), such as arabinogalactans proteins (AGP), are involved in salinity stress [232,233].…”
Section: Adaptations At Protein Levelmentioning
confidence: 87%
See 2 more Smart Citations
“…The same authors noted that transcriptional analyses have indicated a repression of cell wall-related gene expression including AGPs and xyloglucan, as a result of salt stress. Similarly, Azariadis et al [224] reported that immunodetection revealed a weak AGP signal in the 'Koroneiki' cultivar, which was associated with irregular cells and intercellular spaces, resulting in the formation of aerenchyma after 45 days of salt treatment. Hydroxyproline-rich cell wall glycoproteins (HRGP), such as arabinogalactans proteins (AGP), are involved in salinity stress [232,233].…”
Section: Adaptations At Protein Levelmentioning
confidence: 87%
“…The results showed higher levels of MDA and HNE in the 'Arbequina', 'Cobrançosa', 'Pico-Limón' and 'Cornezuelo' cultivars compared with controls, while no significant difference was observed for the 'Changlot Real' and 'Picual' cultivars, renowned for their resistance to salinity. Similarly, Azariadis et al [224] found that MDA levels increased significantly in salt-sensitive varieties ('Koroneiki' and 'Arvanitoli'), but did not occur in tolerant varieties ('Lefkolia' and 'Gaidourelia'), when all were exposed to saline conditions. Meanwhile, in another study, MDA levels in two olive cultivars ('Canino' and 'Sirole') under different salt concentrations remained unchanged [225].…”
Section: Lipid Peroxidationmentioning
confidence: 90%
See 1 more Smart Citation